The impact of fatwas on patients’ acceptance of enamel matrix derivatives for periodontal regeneration in Saudi Arabia - Al-Dabbagh, Najla N (Patient Prefer Adherence, 2018)
BACKGROUND: Since the introduction of enamel matrix derivatives (EMD) (Emdogain(®)), it has not been allowed to be used in Saudi Arabia due to the religious restriction on porcine products. This study was conducted to determine the impact of the fatwas permitting the use of EMD and to assess the general perception of using bone-grafting materials in Jeddah, Saudi Arabia. MATERIALS AND METHODS: This cross-sectional survey study included 213 patients seeking dental treatment at the Faculty of Dentistry Clinics of King Abdulaziz University, Jeddah, Saudi Arabia. They were recruited between September and November 2017. Subjects completed a questionnaire to assess their opinions before and after reading the fatwa about using EMD. RESULTS: Majority of the study subjects (70%) did not accept the use of bone-grafting materials and EMD in periodontal regeneration before reading the fatwas. The highest rate of acceptance was observed for the use of tissues from one’s own body (84%) while the biomaterials of porcine origin had the lowest acceptance rate (14.1%). Strong religious belief and low education level were the two key factors responsible for the initial refusal of EMD use before reading the fatwas. Around 45.1% of the participants changed their opinions in favor of EMD use after reading the fatwas and their interpretations. McNemar’s test found a statistically significant difference in opinions collected before and after reading the fatwas (P<0.001). CONCLUSION: A significant impact of the fatwas was found on patients’ acceptance of EMD use for periodontal regeneration. We believe reliable interpretations of the fatwas may positively shift patients’ attitudes toward using new biomaterials.